Early Life Growth Trajectories in Cystic Fibrosis are Associated with Pulmonary Function at Age 6 Years - Sanders, Don B.; Fink, Aliza; Mayer-Hamblett, Nicole; Schechter, Michael S.; Sawicki, Gregory S.; Rosenfeld, Margaret; Flume, Patrick A.; Morgan, Wayne J. (The Journal of pediatrics, 2015)
To determine whether severity of lung disease at age 6 years is associated with changes in nutritional status before age 6 within individual children with cystic fibrosis (CF). Children with CF born between 1994 and 2005 and followed in the CF Foundation Patient Registry from age ≤2 through 7 years were assessed according to changes in annualized weight-for-length (WFL) percentiles between ages 0 and 2 years and body mass index (BMI) percentiles between ages 2 and 6 years. The association between growth trajectories before age 6 and forced expiratory volume in 1 second (FEV1)% predicted at age 6-7 years was evaluated using multivariable linear regression. A total of 6805 subjects met inclusion criteria. Children with annualized WFL-BMI always >50th percentile (N = 1323 [19%]) had the highest adjusted mean (95% CI) FEV1 at 6-7 years (101.8 [100.1, 103.5]). FEV1 at 6-7 years for children whose WFL-BMI increased >10 percentile points by age 6 years was 98.3 (96.6, 100.0). This was statistically significantly higher than FEV1 for children whose WFL-BMI was stable (94.4 [92.6, 96.2]) or decreased >10 percentile points (92.9 [91.1, 94.8]). Among children whose WFL-BMI increased >10 percentile points, achieving and maintaining WFL-BMI >50th percentile at younger ages was associated with significantly higher FEV1 at 6-7 years. Within-patient changes in nutritional status in the first 6 years of life are significantly associated with FEV1 at age 6-7 years. The establishment of a clear relationship between early childhood growth measurements and later lung function suggests that early nutritional interventions may impact on eventual lung health.